4(x-1)=2(3x-1)(1-2x)

Simple and best practice solution for 4(x-1)=2(3x-1)(1-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)=2(3x-1)(1-2x) equation:



4(x-1)=2(3x-1)(1-2x)
We move all terms to the left:
4(x-1)-(2(3x-1)(1-2x))=0
We add all the numbers together, and all the variables
4(x-1)-(2(3x-1)(-2x+1))=0
We multiply parentheses
4x-(2(3x-1)(-2x+1))-4=0
We multiply parentheses ..
-(2(-6x^2+3x+2x-1))+4x-4=0
We calculate terms in parentheses: -(2(-6x^2+3x+2x-1)), so:
2(-6x^2+3x+2x-1)
We multiply parentheses
-12x^2+6x+4x-2
We add all the numbers together, and all the variables
-12x^2+10x-2
Back to the equation:
-(-12x^2+10x-2)
We get rid of parentheses
12x^2-10x+4x+2-4=0
We add all the numbers together, and all the variables
12x^2-6x-2=0
a = 12; b = -6; c = -2;
Δ = b2-4ac
Δ = -62-4·12·(-2)
Δ = 132
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{132}=\sqrt{4*33}=\sqrt{4}*\sqrt{33}=2\sqrt{33}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-2\sqrt{33}}{2*12}=\frac{6-2\sqrt{33}}{24} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+2\sqrt{33}}{2*12}=\frac{6+2\sqrt{33}}{24} $

See similar equations:

| 7x+21x-8=7(4x+5) | | 166=-4(6x-1)-3x | | s^2+23s+22=0 | | -6(x-8)=90 | | -49-(-45)=x/9 | | 5n+32=-6(3-5n) | | -23-(-38)=x=6 | | 3(1-8a)=195 | | 2w-6=5+3w-3 | | 5x+4x-14=28-5x | | 11.3z+19.24=8.6z–19.92+12.97 | | t^2–14t–15=0 | | k+6/26=1 | | x2=58(x−4) | | w+68=-40 | | 80=10(3+x) | | x/2=5/8(x-4) | | 3(1+3n)+4=61 | | -23-(-38)=x/6 | | -3=-4+m/8 | | 6/x-10=2 | | 8x=-1/12-5/6 | | -8(4+r)=-144 | | g^2–12g+20=0 | | m-4/9=257/90 | | m-13=-10 | | 3(6k-1)=69 | | 5/4=x/2-1/6 | | 2.4z+6.3=-1.7z+47.1 | | -15=k/7 | | x-(-53/5)=41/2 | | 4x+6-10=3x-2 |

Equations solver categories